2015
DOI: 10.1186/s40200-015-0179-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vitamin D deficiency across the spectrum of glucose intolerance

Abstract: BackgroundVitamin D deficiency (VDD) is inversely associated with insulin resistance. We studied the prevalence of VDD across the spectrum of glucose intolerance, including normal glucose tolerance (NGT), prediabetes (PD) and type 2 diabetes (T2D).MethodsWe conducted this cross-sectional, observational study by serially including the PD and T2D patients seen between June and December 2014. We excluded patients with major illness, secondary diabetes and use of vitamin D or glucocorticoids. VDD was defined as se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 22 publications
2
27
1
Order By: Relevance
“…However, recent evidence suggested that vitamin D and calcium homeostasis may also be important for a variety of non-skeletal outcomes. Indeed, multivariate analyses showed a marginally significant inverse association of T2D with dietary calcium intake in American women (13,35). In the prospective studies, low calcium intake was consistently found to be inversely associated with T2D incidence (13,27).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…However, recent evidence suggested that vitamin D and calcium homeostasis may also be important for a variety of non-skeletal outcomes. Indeed, multivariate analyses showed a marginally significant inverse association of T2D with dietary calcium intake in American women (13,35). In the prospective studies, low calcium intake was consistently found to be inversely associated with T2D incidence (13,27).…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, multivariate analyses showed a marginally significant inverse association of T2D with dietary calcium intake in American women (13,35). In the prospective studies, low calcium intake was consistently found to be inversely associated with T2D incidence (13,27). Another investiation by Black Women's Health Study (a prospective cohort study of ~59,000 women aged 21-69 at baseline) found an odds ratio for T2D incidence of 0.82 (0.72-0.93) for highest vs. lowest calcium intake (28).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Modi et al had similar findings in their studies. 17 On the contrary Erdönmez et al, stated that there was no significant association between vitamin D levels and insulin resistance. 18 Also the findings of Sollid et al, suggested that vitamin D supplementation does not improve glycemic status.…”
Section: Discussionmentioning
confidence: 98%